An Exploratory Study Research of Brand Orientation in the Public Sector: The Case of Financial and Development Supervisory Agency (FDSA) - Budiyono, Rochmad (2017)
Marketing is a relevant subject for any organisations since every organisation can have their own customers and products. Thus, marketing is needed not only by the private organisations but also public sector organisation.The differences of characteristic between private and public sector organisations cause the approach to marketing is different for both. Brand orientation and market orientation are marketing methods that have been used by many organisations nowadays. Both of them have been studied in term of the impact on public sector organisations. However, some of the researchers argued that brand orientation is considered as a better way of doing marketing for the public organisations since the market orientation is too much focus on customers. There are many studies has been done in several kinds of the public sector, but there is only limited that discuss the government entities. This project is discussing brand orientation in public sector, specifically in government organisation with Financial and Development Supervisory Agency as a case study